The correspondence of Charles Darwin. Volume 28, 1880 - Darwin, Charles, 1809-1882; Burkhardt, Frederick, 1912-2007; Smith, Sydney, 1911-1988 (Cambridge : Cambridge University Press, 2021)
This volume is part of the definitive edition of letters written by and to Charles Darwin, the most celebrated naturalist of the nineteenth century. Notes and appendixes put these fascinating and wide-ranging letters in context, making the letters accessible to both scholars and general readers. Darwin depended on correspondence to collect data from all over the world, and to discuss his emerging ideas with scientific colleagues, many of whom he never met in person. The letters are published chronologically. In 1880, Darwin published On The Power of Movement in Plants, and began writing his final book, The Formation of Vegetable Mould through the Action of Worms. He was engaged in controversy with Samuel Butler, following publication of his last book, Erasmus Darwin. At the end of the year, he succeeded in raising support for a Civil List pension for Alfred Russel Wallace, co-discoverer of the theory of natural selection.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Darwin, Charles, -- 1809-1882 -- Correspondence; Naturalists -- England -- Correspondence